Analisis Pengaruh Persepsi Kenyamanan, Manfaat, dan Kemudahan Terhadap Sikap Dalam Menggunakan Teknologi Mobilephone (Studi Pada Mahasiswa Pengguna Smartphone di Kota Malang) - Berthus Yudhistira; Ainur Rofiq (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study aims to analyze factors that influence students attitudes on smartphone usage.Analyze focus on how strength perceived enjoyment, perceived usefulness, and perceived ease of use influence on attitude. This study used multiple regression analysis. Questionnaires were distribute into 118 participants. Results showed that the perceived enjoyment, perceived usefulness, and perceived ease of use positively and significanly impact on students attitudes in using smartphone. Keywords: Attitude, mobilephone, Perceived enjoyment, Perceived usefulness, Perceived Ease of use